Antiplatelet/anticoagulant agents and chronic subdural hematoma in the elderly. - Pasquale De Bonis; Gianluca Trevisi; Chiara de Waure; Antonella Sferrazza; Massimo Volpe; Angelo Pompucci; Carmelo Anile; Annunziato Mangiola (PLoS ONE, 2013)
Background and purpose In the last decade there has been an increasing use of antiplatelet/anticoagulant agents in the elderly. The aim of the study was to evaluate the association between exposure to anticoagulant/antiplatelet therapy and chronic subdural haematoma-CSDH. Methods Single institution case-control study involving 138786 patients older than 60 years who visited our academic tertiary care Emergency Department from January 1st 2001 to December 31st 2010. 345 patients with CSDH (cases) were identified by review of ICD-9 codes 432.1 and 852.2x. Case and controls were matched with a 1:3 ratio for gender, age (± 5 years), year of admission and recent trauma. A conditional logistic model was built. A stratified analysis was performed with respect to the presence (842 patients) or absence (536 patients) of recent trauma. Results There were 345 cases and 1035 controls. Both anticoagulant and antiplatelet agents were associated with an increased risk of CSDH with an OR of 2.46 (CI 95% 1.66-3.64) and 1.42 (CI 95% 1.07-1.89), respectively. OR was 2.70 (CI 95% 1.75-4.15), 1.90 (CI 95% 1.13-3.20), and 1.37(CI 95% 0.99-1.90) for patients receiving oral anticoagulants, ADP-antagonists, or Cox-inhibitors, respectively. History of recent trauma was an effect modifier of the association between anticoagulants and CSDH, with an OR 1.71 (CI 95% 0.99-2.96) for patients with history of trauma and 4.30 (CI 95% 2.23-8.32) for patients without history of trauma. Conclusions Anticoagulant and antiplatelet therapy have a significant association with an increased risk of CSDH. This association, for patients under anticoagulant therapy, appears even stronger in those patients who develop a CSDH in the absence of a recent trauma.